2020
DOI: 10.1108/rpj-10-2019-0256
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behaviour and interface evaluation of hybrid MIM/PBF stainless steel components

Abstract: Purpose The paper reports an investigation into the mechanical behaviour of hybrid components produced by combining the capabilities of metal injection moulding (MIM) with the laser-based powder bed fusion (PBF) process to produce small series of hybrid components. The research investigates systematically the mechanical properties and the performance of the MIM/PBF interfaces in such hybrid components. Design/methodology/approach The MIM process is employed to fabricate relatively lower cost preforms in high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…The fracture of the hybrid tensile specimens occurred as a result of the reduced cross section of the tensile samples at the PBF sections, for all sets of samples. This is attributed to the vertical build orientation of the PBF section and to the high UTS of the preforms, and conforms to the reported results [19,55]. In particular, the microstructure of the MIM was optimised after the HIP treatment, as a result of the pore shrinkage and consequently led to an enhanced performance.…”
Section: Mechanical Propertiessupporting
confidence: 89%
See 3 more Smart Citations
“…The fracture of the hybrid tensile specimens occurred as a result of the reduced cross section of the tensile samples at the PBF sections, for all sets of samples. This is attributed to the vertical build orientation of the PBF section and to the high UTS of the preforms, and conforms to the reported results [19,55]. In particular, the microstructure of the MIM was optimised after the HIP treatment, as a result of the pore shrinkage and consequently led to an enhanced performance.…”
Section: Mechanical Propertiessupporting
confidence: 89%
“…The L-PBF sections on top of the MIM preforms, were built using the EOS 316 L stainless steel powder, in particle sizes of 20-65 µm, with the following process parameters: Laser power 180 W; scanning speed 1300 mm/s; energy density 83 J/mm 3 in a protective gas environment to prevent oxidation. The parameters used to build the L-PBF sections and also the details associated with the pre-processing of the preforms and subsequently with the post-processing of hybrid parts are provided in the research reported earlier [19]. Fifteen hybrid tensile bars were produced in this way and then they were split into three sets.…”
Section: The Test Samples' Fabricationmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Surface finish of samples in (a) as deposited and after machining states [62] Fig. 14 Image of the cladding head, touch probe, and end mill co-existing in the tool changer [135] producing small series of hybrid 316L stainless steel components [138]. The mechanical properties and interfaces of such hybrid MIM/LPBF components were investigated and it was reported that they were similar and even better than those of monolithic MIM parts while conforming fully to the ASTM standards for 316L stainless steel parts.…”
Section: Hybrid Additive/machining Solutionsmentioning
confidence: 99%